Peran Organisasi Mahasiswa dalam Meningkatkan Kesadaran Kewarganegaraan di Kalangan Mahasiswa PGSD UNIMED - Nasution, Hajjaziah; Utari, Septi; Siregar, Hanif Luthfi; Aprilia, Nada; Lubis, Putri Ramadhani; Sari, Nopyta; Fadilah, Rizki; Purba, Dearni Asri Br (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research analyzes the role of student organizations in increasing citizenship awareness among students of the Elementary School Teacher Education Study Program, Medan State University. The research method used was qualitative with a descriptive design, involving structured interviews, observation, and documentation. The research subjects consisted of 30 people, namely 20 young members of student organizations and 10 active members. The results showed that student organizations play a significant role in increasing citizenship awareness through educational activities such as seminars and social actions. As many as 85% of respondents claimed that participation in organizational activities helped them understand the values of democracy and diversity. Although most respondents felt the benefits of their involvement, there are still challenges in terms of interest and active participation among students who are not involved. This research emphasizes the importance of educational institutions' support to facilitate activities that can increase civic awareness among students